PENDIDIKAN ISLAM DALAM USAHA MENGATASI KEMISKINAN - Nur Kholis (Jurnal Kependidikan)
Education is an absolute necessity for humans because through education they will acquire higher and exalted position. A country or region will be able to progress and develop if the people having higher knowledge and education. Therefore, education has a really significant role to overcome poverty. As we know, poverty is a common phenomenon in the community. It is a condition where the minimum physical needs for a normal life, especially food and health, cannot be achieved for a relatively long period of time. Poverty can be a very bad thing and give negative impacts on the survival of a person or the public. For that reason, to build a strong community and a strong need to be equipped with education.